Narrative-Based Curriculum Design for Christian Religious Education among Generation Z: A Strategy for Spiritual Value Internalization - Ernida Marbun (Newinera Publisher, 2026)
Digital transformation has significantly reshaped the learning characteristics of Generation Z, directly impacting the effectiveness of Christian Religious Education (CRE). This study aims to develop a narrative-based CRE curriculum model integrated with digital media to support holistic faith formation. The research employs a qualitative approach with a case study design conducted at the Youth Fellowship of the Indonesian Baptist Church of Helvetia, involving 10 respondents. Data were collected through semi-structured interviews, observation, and documentation, and analyzed using thematic analysis. The findings reveal four key themes: (1) mismatch of conventional teaching methods, (2) dominance of visual and digital learning preferences, (3) gap between doctrinal content and lived experience, and (4) effectiveness of narrative approaches in enhancing reflection and value internalization. This study proposes a narrative-based CRE curriculum model integrating cognitive, affective, and experiential dimensions. The novelty lies in the simultaneous integration of narrative pedagogy, digital culture, and spiritual formation within a unified pedagogical framework.